GPCR-mediated effects of fatty acids and bile acids on glucose homeostasis - Oteng, Antwi-Boasiako; Liu, Liu (Frontiers in Endocrinology, 2023)
Fatty acids and glucose are key biomolecules that share several commonalities including serving as energy substrates and as signaling molecules. Fatty acids can be synthesized endogenously from intermediates of glucose catabolism via de-novo lipogenesis. Bile acids are synthesized endogenously in the liver from the biologically important lipid molecule, cholesterol. Evidence abounds that fatty acids and bile acids play direct and indirect roles in systemic glucose homeostasis. The tight control of plasma glucose levels during postprandial and fasted states is principally mediated by two pancreatic hormones, insulin and glucagon. Here, we summarize experimental studies on the endocrine effects of fatty acids and bile acids, with emphasis on their ability to regulate the release of key hormones that regulate glucose metabolism. We categorize the heterogenous family of fatty acids into short chain fatty acids (SCFAs), unsaturated, and saturated fatty acids, and highlight that along with bile acids, these biomolecules regulate glucose homeostasis by serving as endogenous ligands for specific G-protein coupled receptors (GPCRs).Activation of these GPCRs affects the release of incretin hormones by enteroendocrine cells and/or the secretion of insulin, glucagon, and somatostatin by pancreatic islets, all of which regulate systemic glucose homeostasis. We deduce that signaling induced by fatty acids and bile acids is necessary to maintain euglycemia to prevent metabolic diseases such as type-2 diabetes and related metabolic disorders.